2014
DOI: 10.1519/jsc.0b013e3182986a4c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactate Supplementation and Sodium Bicarbonate on 40-km Cycling Time Trial Performance

Abstract: 39The use of nutritional supplements to improve sporting performance and increase training 40 adaptations is commonplace amongst athletes and is an expanding market in terms of product 41 choice and availability. The purpose of this study was to examine the effects of two ergogenic 42 aids with extracellular blood buffering potential, namely sodium bicarbonate (NaHCO 3 ) and a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 38 publications
(68 reference statements)
3
25
3
4
Order By: Relevance
“…Despite this, the reported effects are equivocal, with several studies reporting no effect on exercise performance and capacity 3,4,5,6,7 . Inconsistencies in the performance outcomes of sodium bicarbonate supplementation studies can be partly attributed to differing dosing regimens 4 , gastrointestinal (GI) discomfort experienced by some participants 8 , exercise models insufficient to be limited by hydrogen cation (H + ) accumulation 5 and individual variation in the response to supplementation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the reported effects are equivocal, with several studies reporting no effect on exercise performance and capacity 3,4,5,6,7 . Inconsistencies in the performance outcomes of sodium bicarbonate supplementation studies can be partly attributed to differing dosing regimens 4 , gastrointestinal (GI) discomfort experienced by some participants 8 , exercise models insufficient to be limited by hydrogen cation (H + ) accumulation 5 and individual variation in the response to supplementation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Morris et al (2011) reported that consuming 120 mg/kg of body mass of lactate increased blood bicarbonate levels and improved exercise performance during high-intensity cycling ergometry to exhaustion. However, previous investigators who examined the effect of lactate supplementation on simulated cycling time trial performances, have been unable to provide evidence to support the LS theory (Bryner et al, 1998;Northgraves et al, 2014;Peveler & Palmer, 2012;Swensen et al, 1994). These mixed findings may be due to differences in exercise intensity, duration, and testing modalities (i.e., single exercise bouts versus repeat trials, time to exhaustion versus time trials).…”
Section: Introductionmentioning
confidence: 95%
“…Commercially available forms of nutritional ergogenic aids include sodium bicarbonate, β-alanine, and lactate supplements. An extensive review by McNaughton, Siegler, and Midgley (2008) highlighted more than 12 investigations demonstrating that chronic sodium Jourkesh, Ahmaidi, Keikha, Sadri, & Ojagi, 2011;McNaughton et al, 2008), there is mixed support for the use of lactate supplementation to improve aerobic performance (Bryner, Hornsby, Chetlin, Ullrich, & Yeater, 1998;Morris, Shafer, Fairbrother, & Woodall, 2011;Northgraves, Peart, Jordan, & Vince, 2014;Peveler & Palmer, 2012;Swensen, Crater, Bassett, & Howley, 1994). According to the lactate shuttle (LS) theory, lactate can be utilized in the Cori cycle of the liver and/or skeletal muscle, to synthesize glycogen or be converted into pyruvate and enter aerobic metabolism (Brooks, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme a literatura tem apresentado, os estudos que investigaram o lactato, como um substrato energético, não apresentaram melhora no desempenho aeróbio (BRYNER et al, 1998;NORTHGRAVES et al, 2014;PEVELER e PALMER, 2012;SWENSEN et al, 1994). Contudo, apenas um estudo apresentou resultados positivos, com uma grande melhora de 25% no desempenho aeróbio (AZEVEDO et al, 2007).…”
Section: Suplementação De Bicarbonatounclassified